Pathways to Unsegregated Sharing of Airspace: Views of the Uncrewed Aerial Vehicle (UAV) Industry - Matt Grote; Aliaksei Pilko; James Scanlan; Tom Cherrett; Janet Dickinson; Angela Smith; Andy Oakey; Greg Marsden (Drones, 2021)
The uncrewed aerial vehicle (UAV or drone) industry is expanding, offering services such as video/photography, inspection, monitoring, surveying, and logistics. This is leading to competing demands for airspace with existing crewed aircraft activities, especially in uncontrolled airspace. As a result, there is an increasingly urgent need for a shared airspace solution that enables drones to be integrated with the wider aviation community in unsegregated operations. The purpose of this research was to engage with the drone industry to understand their issues regarding shared airspace as an important first step in the co-development of operating procedures that can provide equitable airspace access for all. An online, interactive workshop format was employed, with participants (n ~ 80) drawn from the UK drone industry and other attendant organisations. Verbal and written data were recorded, and then analysed using thematic analysis. The findings summarise the issues on a range of topics, grouped into three over-arching themes: (1) operational environment; (2) technical and regulatory environment; and (3) equity and wider society. Results suggested that important issues included the necessity for a dependable detect-and-avoid (DAA) system for in-flight de-confliction, based on onboard electronic conspicuity (EC) devices, and the need for support for shared airspace from the wider aviation community. This study contributes to the stakeholder engagement that will be essential if the co-development of a shared airspace solution is to be widely acceptable to all.